Study of Biogas Production Rate from Water Hyacinth by Hydrothermal Pretreatment with Buffalo Dung as a Starter - Teguh Kurniawan; Yuhelsa Putra; Dewi Murni (Diponegoro University, 2014)
In this paper we report the effects of hydrothermal pretreatment on biogas enhancement production rates from water hyacinth mixed with buffalo dung. The focus of the experiment was on the time of hydrothermal pretreatment and the ratio of water hyacinth with buffalo dung. The hydrothermal pretreated substrates were characterized by TDS, BOD and pH. The hydrothermal pretreatment of 60 minutes with the ratio of water hyacinth to buffalo dung 1:2 showed the highest biogas production rate at 7889 ml/day. However, the highest methane composition was 52.82% which resulted on the hydrothermal treatment of 30 minutes with equal ratio of water hyacinth and buffalo dung. Thus, the optimum of methane yield obtained at hydrothermal pretreatment for 30 minutes with equal ratio of water hyacinth to buffalo dung is 2856 ml/day. The hydrothermal pretreatment increases the rate production of biogas 102% and the methane yield 51% relative to untreated water hyacinth. The ratio of water hyacinth and buffalo dung has a great impact on biogas production rate and compositions for hydrothermal pretreated substrates.